Geologi, Genesis dan Karakteristik Endapan Laterit Bauksit di Daerah Melugai, Kalimantan Barat - Muhammad Hery; Rosana, Mega Fatimah; Hutabarat, Johanes; Hartono, Hill Gendoet (ReTII, 2025)
Lateritic bauxite deposits found in Melugai Village, West Kalimantan, are located within a prospective laterite zone. This study aimed to investigate the geological setting and genesis of the bauxite deposits to determine their controlling factors and resulting characteristics. Methods included geological mapping, petrographic analysis, and laboratory tests (XRD and XRF). The Melugai area is underlain by the Triassic Pinoh Metamorphic Rocks, specifically metatuff and metaandesite units. Geomorphologically, the region features gently sloping to inclined undulating hills with a dendritic drainage pattern. Bauxite formation is primarily controlled by parent rock type, time, tropical climate, and low-relief geomorphology. The lateritization process intensifies weathering and leaching of soluble elements (Na, K, Ca), leaving a residue rich in aluminum hydroxide (Al(OH)₃) that subsequently hardens into bauxite. The deposits are classified into two types based on their parent rock. XRD analysis identified dominant minerals: gibbsite, hematite, goethite, kaolinite, quartz, and sodalite. XRF analysis revealed a significant difference in quality. Bauxite derived from metatuff has an average Al₂O₃ content of 47.53% (medium grade), while bauxite from metaandesite has an average Al₂O₃ content of 32.25% (low grade). It is concluded that bauxite sourced from the metatuff parent rock exhibits better quality and a stronger degree of laterization.